Lilly's February love - Irvin, Kelly (Amish romance birthday series, 2026)
She feels guilty simply talking to him. He dumped his special friend and his faith to flee his community. Yet her heart insists he's the one. It's Lilly Plank's birthday, and she's no closer to marriage than she was the previous year. She happily cares for her ailing parents, but she still secretly longs for a certain man -- one she can never have. Josiah Shrock once courted Lilly's sister. Then he left Jamesport with no explanation. Shortly after Lilly's birthday, her brothers hire Josiah, who's returned to Jamesport to reclaim his Amish heritage, to manage their father's farm. Now the two must work together every day. Lilly struggles to ignore her reignited feelings for him. Josiah's feelings grow despite his efforts to remain at arm's length. Together Lilly and Josiah face painful family upheaval. Only by trusting God and each other can they receive the beautiful birthday gift He has planned for them.